Measurements of indirect CP asymmetries in D0→K-K+ and D0→π-π+ decays - Aaij, Roel; Bien, Alexander; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Physical review letters, 2014)
A study of indirect CP violation in D0 mesons through the determination of the parameter AΓ is presented using a data sample of pp collisions, corresponding to an integrated luminosity of 1.0 fb−1, collected with the LHCb detector and recorded at the center-of-mass energy of 7 TeV at the LHC. The parameter AΓ is the asymmetry of the effective lifetimes measured in decays of D0 and ¯D0 mesons to the CP eigenstates K−K+ and π−π+. Fits to the data sample yield AΓ(KK)=(−0.35±0.62±0.12)×10−3 and AΓ(ππ)=(0.33±1.06±0.14)×10−3, where the first uncertainties are statistical and the second systematic. The results represent the world’s best measurements of these quantities. They show no difference in AΓ between the two final states and no indication of CP violation.
Im Titel sind die Zahl "0" und das Zeichen "-" und "+" hochgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, C. Färber, E. Gersabeck, L. Grillo, S. Hansmann-Menzemer, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 02.11.2020